Influence of Processing Type in the Morphology of Membranes Obtained from PA6/MMT Nanocomposites - Rodholfo da Silva Barbosa Ferreira; Caio Henrique do Ó Pereira; Rene Anisio da Paz; Amanda Melissa Damião Leite; Edcleide Maria Araújo; Hélio de Lucena Lira (Advances in Materials Science and Engineering)
The nanocomposites have an extensive use in the current process of membrane preparation, taking into account their unique features as membranes. Thus, the study of nanocomposite processing to obtain membranes is highly important. In this work, Brazilian clay was used (Brasgel PA) for the preparation of polyamide/clay nanocomposite. The nanocomposites were produced in a high rotation homogenizer and in a twin screw extruder. From the nanocomposites and pure polymers processed in the two equipments, membranes were prepared by the immersion-precipitation method, using formic acid as solvent. By X-ray diffraction (XRD), the formation of exfoliated and/or partially exfoliated structures with changes in the crystalline phases of the polyamide was observed. From scanning electron microscopy images, it was observed that the processing clearly influenced the membrane morphology.